Pembelajaran Menulis Dengan Menggunakan Teknik Clustering - Endah Anisa Rahma (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2018)
Writing is a productive skill which means that it is a process of exploring one’s mind into words in a good grammar. The objective of this study is to look at some given theories or research on the use of clustering technique for writing skill. The discussion of the approach is focused on a clustering technique as the pre-writing technique should be used in teaching writing for second grade of junior high school students. The study found that clustering technique is very effective used in pre-writing stage because it can stimulate idea in writing process. Teaching writing by using clustering technique is one of technique that gives positive impact to the success of teaching writing because it is a strategy for the students to begin writing with exploring the ideas. It is also found that the studentsare highly motivated to learn the language by using clustering technique. The method used in this study is library research. Readings obtained from various are processed and described in a descriptive way. Based on the research findings and experts’ statements, it is found that clustering technique is effective to enhance the students’ writing skill. This study is expected to be useful for other English teachers and readers.